PENGARUH PENGGUNAAN MEDIA SOSIAL FACEBOOK TERHADAP HASIL BELAJAR PESERTA DIDIK MATA PELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) - Ulum, Moh Saeful; Tsaronny, Muhammad Al Ghiffarie (THORIQOTUNA: Jurnal Pendidikan Islam, 2019)
This study aims to determine the influence of the use of facebooktoward student learning outcomes on Islamic Education at SDN 3Tanjungkerta. The method used in this study is a quantitativedescriptive method, because the data or research sample are bothnormal distribution variables, then the correlation coefficient uses theSpearman rank (rs) or rank. The results of this study for variable X(Facebook usage) are the degree of determination is 53.39%, while46.61% is influenced by other factors. The results of the significancetest or hypothesis test show that tcount (4.71) is greater than ttable,(1.72) so that Ha (Alternative Hypothesis) is accepted and H0 (ZeroHypothesis) is rejected. It means that the influence of using facebooktoward student learning outcome is very high enough.